Odpowiedzi

2010-01-25T17:06:58+01:00
(b-1)² =b²-1
(5-x)² =25-x²
(4a-b)² =16a²-b²
(tw - 7 )² =tw²-49
(1/4 p - 2)² =1/8p²-4
(10k-1/5 m ) ² =100k²-1/25m²
(√5 - 3x)² =5-9x²
(3√7 - 2√7 a ) ² =21-28a²
(5 p ² - 3p ) ² =25p do 4 -9p²
(0,4x ³ y² - 5x)² =0.16x do 5 y do 4 - 25x²
(6 t ² w - 1/3w ²)² =36t do 4 w² - 1/9w do 4

Liczę na naj;p

1 5 1
2010-01-25T17:17:44+01:00
(b-1)² = b²-2b+1
(5-x)² =25-10x+x²
(4a-b)² =16a²-8ab+b²
(tw - 7 )² =(tw)²-14tw+49
(1/4 p - 2)² =1/16p²-p+4
(10k-1/5 m ) ² =100k²-4mk+1/25m²
(√5 - 3x)² =5-6√5x+9x²
(3√7 - 2√7 a ) ² =63-84a+28a²
(5 p ² - 3p ) ² =25p²-30p³+9p²
(0,4x ³ y² - 5x)² =0.64x³-4x³y²+25x²
1 5 1